2017
DOI: 10.1016/j.jval.2017.08.2302
|View full text |Cite
|
Sign up to set email alerts
|

Calculating The Indirect Costs Of Adult Pneumococcal Disease And The Rate Of Return To The 13-Valent Pneumococcal Conjugate Vaccine (PCV13) In Older Adults, With An Application To Denmark

Abstract: A787 and exceed 20 times DCs for OCAP. ICs consist largely of nonmarket productivityspecifically housework-lost to death. The RoR to PCV13 in the general older adult population is 149% and is driven by averted ICAP-related costs. In elderly diabetics, ICs per episode are higher and the RoR a stunning 1,191%. Main results are robust in sensitivity analyses. ConClusions: The ICs of pneumococcal disease are considerable, even among older retired adults. The RoR to PCV13 in Danish older adults is high, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In general, the literature on this topic is not numerous, although research has been found from Denmark, Switzerland, Turkey or the United States. [19,20,21,22] The US authors indicate that vaccinations against pneumococcus allow savings in indirect costs exceeding 70% savings in direct costs. [22] According to the Turkish researchers, indirect costs account for 21%, 26% and 84% of of pneumococcal meningitis, pneumonia and OM total costs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature on this topic is not numerous, although research has been found from Denmark, Switzerland, Turkey or the United States. [19,20,21,22] The US authors indicate that vaccinations against pneumococcus allow savings in indirect costs exceeding 70% savings in direct costs. [22] According to the Turkish researchers, indirect costs account for 21%, 26% and 84% of of pneumococcal meningitis, pneumonia and OM total costs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… Country Author (Ref.) Analysis type Intervention Comparator Assessment Austria Walter et al 110 BIM PCV13 or PPV23 None Positive Belgium Marbaix et al 71 CUA PCV13 None Positive Belgium Willem et al 112 CUA PPV23 PCV13+PPV23 Positive Denmark Sevilla et al 95 CA PCV13 NR Positive Denmark Birck et al 41 CEA PPV23 None Positive EU* Esposito et al 52 CA NR NR Positive Finland THL 103 CEA NR NR NR France HCSP 59 CUA PCV13+PPV23 PPV23 Positive Germany Kuchenbecker et al 67 <...…”
Section: Health Economic Evidencementioning
confidence: 99%
“…While MenB's education-related costs can lead to losses in lifetime productivity, MenB can also impact productivity more directly when its burdens extend into working ages. MenB can lead to missed workdays and can hinder productivity while at work (94,99). All of this can lead to missed opportunities for work-related skill development or career advancement.…”
Section: Labor Market Productivity Gainsmentioning
confidence: 99%
“…In addition to market productivity, which involves paid work, MenB also impacts non-market productivity, which involves unpaid work. Specifically, MenB can impact patients' ability to spend time volunteering, caregiving, and doing housework and can impact their productivity while working on such activities (99).…”
Section: Non-market Productivity and Leisure Gainsmentioning
confidence: 99%